Pelatihan Tarian Tradisional Tor-Tor Dalam Pelestarian Budaya Di Jorong Taming Batahan Nagari Barat Kecamatan Ranah Batahan - Ulfa Aida; Wahyu Azali (MADANI PUBLISHER INDONESIA, 2025)
This research aims to reveal and explain the existence of the traditional tor-tor dance in Jorong Taming Batahan, Ranah Batahan District, West Pasaman Regency in the current era, especially at weddings. From this research we know that the tor-tor dance was brought by the ancestors of the Mandailing tribe, Mandailing Natal district, North Sumatera who migrated to West Pasaman and also mixed marriages between the native West Pasaman people and Batak immigrants which further strengthened the tor-tor dance culture.